2011
DOI: 10.3168/jds.2010-3361
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a perennial ryegrass diet or total mixed ration diet offered to spring-calving Holstein-Friesian dairy cows on methane emissions, dry matter intake, and milk production

Abstract: The objective of the present study was to compare the enteric methane (CH4) emissions and milk production of spring-calving Holstein-Friesian cows offered either a grazed perennial ryegrass diet or a total mixed ration (TMR) diet for 10 wk in early lactation. Forty-eight spring-calving Holstein-Friesian dairy cows were randomly assigned to 1 of 2 nutritional treatments for 10 wk: 1) grass or 2) TMR. The grass group received an allocation of 17 kg of dry matter (DM) of grass per cow per day with a pre-grazing h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
75
3
2

Year Published

2012
2012
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(84 citation statements)
references
References 42 publications
4
75
3
2
Order By: Relevance
“…This decrease in predicted methane emissions could be explained by a decrease in feed intake when temperature increases during summer (Hammami et al 2015) and also because the majority of dairy cows in the Walloon Region of Belgium are outdoors grazing in the summer period. In general, dry matter intake of grass-fed cows is expected to be lower compared with cows fed with a total mixed ration (Robertson and Waghorn 2002) leading to a decrease of methane emissions (O'Neill et al 2011) because dry matter intake represents the main driver of methane production (Hegarty et al 2007). The majority of cows used in this study calved during autumn (36% of cows calved in September, October, or November).…”
Section: Prediction Of Methane Emissionsmentioning
confidence: 99%
“…This decrease in predicted methane emissions could be explained by a decrease in feed intake when temperature increases during summer (Hammami et al 2015) and also because the majority of dairy cows in the Walloon Region of Belgium are outdoors grazing in the summer period. In general, dry matter intake of grass-fed cows is expected to be lower compared with cows fed with a total mixed ration (Robertson and Waghorn 2002) leading to a decrease of methane emissions (O'Neill et al 2011) because dry matter intake represents the main driver of methane production (Hegarty et al 2007). The majority of cows used in this study calved during autumn (36% of cows calved in September, October, or November).…”
Section: Prediction Of Methane Emissionsmentioning
confidence: 99%
“…Several studies have reported that feed intake is the principal determinant of enteric CH 4 emissions from cattle (Mills et al, 2003;Hegarty et al, 2007;O'Neill et al, 2011). In addition, feed intake is also a key variable required to quantify CH 4 and N 2 O emissions from manure (Basset-Mens et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, grass grazed in situ in the early and late grazing season is a higher-quality more digestible feed than the grass silage, which is the main feed, once animals are housed. The higher digestible feed leads to improvements in animal productivity as well as reductions in the proportion of dietary energy lost as methane and a reduction in methane per unit of output (O'Neill et al, 2011). The shorter housing season also leads to reduced slurry methane (CH 4 ) and nitrous oxide (N 2 O) emissions from storage, as quantities stored will be lower.…”
Section: Criteria Included In the Carbon Navigatormentioning
confidence: 99%